Seismic behavior of two exterior beam–column connections made of normal-strength concrete developed for precast construction. (15th September 2015) - Yuksel, Ercan; Karadogan, H. Faruk; Bal, İ. Engin and Ilki, Alper and Bal, Ahmet and Inci, Pınar
Highlights: Two types of new precast beam–column connections are studied experimentally. The improved behaviors are obtained with making some minor modifications in details. The tested specimens are numerically modeled to calibrate the analytical tools. Abstract: The lack of in-depth understanding of the seismic behavior and ductility of precast concrete structures makes it difficult to reach to ductility demand which could be exhibited during an earthquake. The limitations are mainly related to the beam-to-column connections as the main load transfer paths. Two distinct exterior beam–column connections made of normal-strength concrete are investigated experimentally. Both dry and wet type installment techniques are used in the industrial type joints while the residential type joints are wet connections. The specimens are subjected cyclic displacement reversals in order to obtain information on strength, stiffness and ductility characteristics of the connection details. The preliminary design of the joints has been updated during the tests based on the damages observed, thus a set of improved specimens have also been built and tested, and a relatively better performance is obtained expectedly. The industrial and residential types of connections showed stable load–displacement cycles with high energy dissipation up to structural drift of 2%, though a significant level of pinching and deterioration of the critical section have occurred at around 3% drift level. The tested specimens have been numerically modeled to calibrate the analytical tools, and a satisfactory approximation has been obtained between experimental and numerical results.